PUSAT EDUKASI PENANGANAN SAMPAH DI KOTA BANJARMASIN - Trisar Akmal Irhamna; Akbar Rahman (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2026)
The increasing volume of waste in Banjarmasin is not supported by adequate public awareness and knowledge regarding responsible waste management, indicating the need for an educational facility capable of delivering environmental information in a more engaging and accessible way. The design of the Waste Management Education Center adopts a recreational education concept, presenting environmental learning through interactive, inclusive, and enjoyable spatial experiences. Using the Architectural Programming method, the project integrates creative workshops, educational pathways, and visual elements made from recycled materials that function as environmental communication media. By applying sustainable architectural principles across environmental, social, and economic aspects, this facility aims to enhance public awareness while serving as an educational destination that encourages long-term behavioral change toward sustainable waste management.